2014
DOI: 10.1016/j.livsci.2014.01.033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cow nutrient status during the second and third trimesters on age at puberty, antral follicle count, and fertility of daughters

Abstract: a b s t r a c tFluctuating feed resources to beef cows across the production cycle is a proven method for decreasing input costs; however, limiting nutrients during late gestation have been demonstrated to decrease ovarian follicle numbers in female offspring in some studies. We hypothesize that limiting nutrients to mature ( Z3 yr) crossbred beef cows during the second and third trimesters would result in daughters that would have decreased follicle numbers detectable by ultrasonography as yearlings. Over fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 20 publications
1
35
0
4
Order By: Relevance
“…Previous studies (Sullivan et al, 2009;Mossa et al, 2010;Echternkamp et al, 2012) have reported that nutritional manipulation during early gestation in first-parity dams can impact ovarian antral follicle count in their female progeny. In contrast, however, Cushman et al (2014) reported no differences in antral follicle count of heifer progeny of mature cows that were fed 75, 100, or 125% of NRC maintenance requirements during the last 2 trimesters of pregnancy. Although progeny in the current study were from first-parity dams and only prepubertal antral follicle counts were obtained, results from the current dataset is consistent with those of Cushman et al (2014), who reported no differences in antral follicle counts obtained in progeny at 14 mo of age.…”
Section: Reproductive Tract Development Follicular Waves and Pubertymentioning
confidence: 86%
See 3 more Smart Citations
“…Previous studies (Sullivan et al, 2009;Mossa et al, 2010;Echternkamp et al, 2012) have reported that nutritional manipulation during early gestation in first-parity dams can impact ovarian antral follicle count in their female progeny. In contrast, however, Cushman et al (2014) reported no differences in antral follicle count of heifer progeny of mature cows that were fed 75, 100, or 125% of NRC maintenance requirements during the last 2 trimesters of pregnancy. Although progeny in the current study were from first-parity dams and only prepubertal antral follicle counts were obtained, results from the current dataset is consistent with those of Cushman et al (2014), who reported no differences in antral follicle counts obtained in progeny at 14 mo of age.…”
Section: Reproductive Tract Development Follicular Waves and Pubertymentioning
confidence: 86%
“…In contrast, however, Cushman et al (2014) reported no differences in antral follicle count of heifer progeny of mature cows that were fed 75, 100, or 125% of NRC maintenance requirements during the last 2 trimesters of pregnancy. Although progeny in the current study were from first-parity dams and only prepubertal antral follicle counts were obtained, results from the current dataset is consistent with those of Cushman et al (2014), who reported no differences in antral follicle counts obtained in progeny at 14 mo of age. Moreover, in the current study, heifer progeny from DG-treated dams were significantly heavier at birth (Gunn et al, 2014b); however, no differences were observed in antral follicle counts between treatments, and birth BW and antral follicle count were not correlated.…”
Section: Reproductive Tract Development Follicular Waves and Pubertymentioning
confidence: 86%
See 2 more Smart Citations
“…However, the exact mechanism of how AFC is mediated is unknown. Cushman et al (2014) suggested that AFC may be predetermined before birth, and may also be influenced through developmental programming. Yet, to our knowledge this study and research by Gunn et al (2014b) are the first reports suggesting that postnatal diet may alter AFC.…”
Section: Protein Amount and Bovine Ovarian Functionmentioning
confidence: 99%